(untitled) (REMUNOM, 2024)
In recent years, there has been a notable increase in cases of Autism Spectrum Disorder (ASD) in varying degrees of severity. Autism is characterized by impairments in the development of social and communicative skills, stereotyped behavior and restricted interests. Research has sought to relate some vitamins and minerals to the treatment of ASD symptoms. The present study aims to discuss Autism Spectrum Disorder and its relationship with vitamin D. This is research based on a qualitative and descriptive bibliographical survey, through books, informative articles and publications in scientific databases. Nutritional treatment is also fundamental, considering that autistic people have important characteristics that directly impact their diet. Vitamin D supplementation improves typical symptoms of autism spectrum disorder, as indicated by reduced scores on the scales. However, more studies and research are needed to focus on the vitamin D profile in children with ASD and its supplementation in clinical practice.